2007
DOI: 10.1007/s10681-007-9571-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitotic inhibitors and genotype on chromosome doubling of Rosa

Abstract: Dinitroanilines represent a class of compounds that are widely used in herbicide formulations as they depolymerise plant microtubles, causing chromosome doubling. The potential of microtubule depolymerising herbicides triXuralin, oryzalin, and amiprophosmethyl (APM) for in vitro chromosome doubling of Rosa was studied. Five concentrations (0, 3, 6, 12 and 24 M) and three exposure periods (12, 24 and 48 h) for each of the compounds were compared. Oryzalin, triXuralin and APM were not signiWcantly diVerent in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…The authors also reported a reduction in plant growth from 0 to 45% (control and 10 mM) and 0 to 100% (control and 60 µM) in the colchicine and oryzalin treatments, respectively. Reduced survival of banana (Costa et al, 2011) and rose explants (Khosravi et al, 2008) was also observed with the use of oryzalin. In contrast, colchicine promotes a greater recovery rate of stable tetraploids in Eriobotrya japonica (Thunb.)…”
Section: Effect Of Oryzalin Concentration and Exposure Time On Cassavmentioning
confidence: 97%
See 2 more Smart Citations
“…The authors also reported a reduction in plant growth from 0 to 45% (control and 10 mM) and 0 to 100% (control and 60 µM) in the colchicine and oryzalin treatments, respectively. Reduced survival of banana (Costa et al, 2011) and rose explants (Khosravi et al, 2008) was also observed with the use of oryzalin. In contrast, colchicine promotes a greater recovery rate of stable tetraploids in Eriobotrya japonica (Thunb.)…”
Section: Effect Of Oryzalin Concentration and Exposure Time On Cassavmentioning
confidence: 97%
“…These results suggest that there are different levels of sensitivity to colchicine depending on the cassava variety used in the treatments. Khosravi et al (2008) reported that the success in chromosomal doubling in rose depends on the genotype evaluated and the ploidy level of the species, where low ploidy levels were more prone to chromosomal doubling. According to these authors the application of 6 µM oryzalin for 24 h in Rose persica (2n = 2x), R. hybrida cv Iceberg (2n = 3x) and R. hybrida cv Akito (2n = 4x) resulted in 60.0, 6.3, and 0% of chromosomal doubling, respectively.…”
Section: Effect Of Colchicine On the Survival Of Cassava Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Praça et al (2009) also employed the shoot tip as a source of explants for in vitro polyploidization of Stupické with no death records for the distinct treatments. Khosravi et al (2008) reported that the efficiency of polyploidization depends on the type of explant and its interaction with the anti-mitotic agent. According to Roy et al (2001) and Praça et al (2009), colchicine is adequate for in vitro induction of polyploids.…”
Section: Nuclear 2c Value and Karyotype Of 'Santa Cruz Kada Gigante'mentioning
confidence: 99%
“…However, nowadays, colchicine is gradually substituted by other antimitotic agents due to its toxicity to humans by binding specifically to animal tubulin dimers. It was reported that antimicrotubule herbicides such as trifluralin are more specific for plant tubulin and mitosis in vitro compared to colchicine, and that these chemicals are at least as efficient as colchicine in chromosome doubling, but were less phytotoxic (Mu and Cao, 1999;Khosravi et al, 2008). However, for herbicides, the concentration is the key issue in their application.…”
Section: Introductionmentioning
confidence: 99%